On the principles of allocation of concessional finance, in particular from Multilateral Development Banks - Patrick Guillaumont (Fondation pour les études et recherches sur le développement international (FERDI), 2023)
Allocation is here understood as allocation among countries, while it is sometime taken as allocation between projects or operations. Intercountry allocation is an essential issue for concessional resources that are scarce. This note presents few remarks on the allocation of concessional resources an issue that has until now been rather neglected compared to their mobilization, although the two are interlinked2 . Since MDBs are the main supplier of these resources to countries, and, as multilateral, should have agreed and transparent rules of allocation, the following remarks mainly apply to them.
Keywords: 330; Vulnerabilities; Aid allocation